Record of Ragnarok. Volume 8 - Umemura, Shin'ya; Fukui, Takumi (Viz signature., 2023)
"Once every millennium, the gods assemble to decide if humanity is worthy of its continued existence or if it should be destroyed! When the verdict is destruction, the final battle between the gods and mortal heroes will decide the survival or extinction of the human race--a battle known as Ragnarok! Round four of Ragnarok has ended in a shocking win for humanity, with Jack the Ripper standing victorious over the fallen Heracles. With the score now tied, the gods are absolutely determined not to let humanity get ahead. Raring to go since the start, Shiva, the Destroyer, finally gets his chance to enter the Valhalla arena. With an opportunity to take the lead, Brunhilde calls upon the unbridled strength of the greatest (and horniest) sumo wrestler in history, Raiden Tameemon!"--